Leadership Model in Influencing the Performance of Rural Government Officials - Rizca Yunike Putri; Ahmad Sufaidi; Silvia Nur Nabiilah; Silvi Rahmawati; Novita Sari Fikana; Rehan Kautsar Amara (Program Studi Ilmu Politik Fakultas Ilmu Sosial dan Ilmu Politik Universitas PGRI Ronggolawe Tuban, 2023)
The village as a community unit protected by law has territorial boundaries with the authority and power to regulate and manage government affairs in the village environment, the interests and needs of the local community based on community initiative and deliberation, rights of origin, as well as recognized customary or traditional rights. and respected in the government system of the Republic of Indonesia. As a village area whose jurisdiction is recognized, it has the authority to regulate and manage the interests of the local community, based on local origins and traditional customs, which are recognized or formed in the National government system in the districts of each province. However, villages with various resources and potential have leadership problems where leadership factors, especially in villages, are able to influence and maximize community participation in village development. The leadership model that can be implemented and used by a leader in leading his citizens and in increasing village community participation in development will influence the intensity of community participation that will be given to development in his village. The village head is a political position that must go through a legitimized election stage in general elections at the village level. PERMENDAGRI No. 72 of 2020 concerning the Second Amendment to Minister of Home Affairs Regulation Number 112 of 2014 concerning Election of Village Heads states that the village head is a village official elected by the village community with a term of office of 6 years. The method used in this activity uses a Participatory Action Research (PAR) approach with a focus on Action Learning (8). Action Learning or AL in the realm of PAR is understood as the delivery of core material in activities through direct practice.